The Association of Gestational Hypertension With the Incidence of Low Birth Weight at Harapan Bunda Hospital, Batam City - Nadya Amelia,; Catur Yulinawati,; Inke Asmika, (International Journal Of Health Science, 2025)
Low birth weight babies (LBW) are babies who weigh <2500 grams regardless of gestational age or gestation period. Gestational hypertension can continue into labor which will cause fetal growth disorders that will affect the baby's birth weight so that mothers who have high blood pressure have a higher risk of giving birth to low birth weight babies. This study was conducted to determine the relationship between gestational hypertension and the incidence of low birth weight at Harapan Bunda Hospital, Batam City. Methods: This study is a quantitative study with an observational analytic approach using a Case Control design with a retrospective approach. The population in this study were all babies born at Harapan Bunda Hospital Batam. The number of samples taken was 30 babies and used purposive sampling technique using a Checklist sheet. Data analysis using chi-square test. From the statistical results using the Chi Square statistical test with a meaning value of a=0.05, the p value = 0.027 means that there is a relationship between gestational hypertension and the incidence of low birth weight and the magnitude of the Odds Ratio (OR) value is 2.333, meaning that mothers who have a history of gestational hypertension or who experience hypertension during pregnancy have a 2.333 times greater chance of giving birth to babies with low birth weight.